Superficial Temporal Artery-Middle Cerebral Artery Bypass (STA-MCA) for Middle Cerebral Artery Dissecting Aneurysm in a Child - Chowdhury, Forhad Hossain; Haque, Md Raziul; Islam, Md Shafiqul; Sarker, Asit Chandra; Alam, Sarwar Morshed (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Intracranial arterial dissection or dissecting aneurysm is relatively uncommon and usually involve the vertebrobasilar system. Here we report a pediatric case of middle cerebral artery dissection/dissecting aneurysm with sub arachnoid hemorrhage and Sylvian fissure hematoma on dominant side. After initial evacuation of hematoma, we went for trapping and excision of dissection/dissecting aneurysm followed by STA-MCA bypass. Patient recovered fully from her neurological deficit. Probably this is the first reported case of STA-MCA bypass in Bangladesh. J Bangladesh Coll Phys Surg 2014; 32: 94-98